Monsters and their meanings in early modern culture - Williams, Wes (Oxford University Press, 2011)
Wes Williams explores the place of monsters in the early modern imagination, charting the migration of the monstrous from natural history to moral philosophy, from descriptions of creatures found in the external world to the drama of human motivation, of sexual and political identity.
10.1093/acprof:oso/9780199577026.001.0001
Keywords: French literature; Monsters in literature; European literature; Science; Art; European; Monsters in art